(untitled) (Perner’s Contacts, 2014)
This article analyses safety of commercial air transport and its economic impact. It gives description of organizations which are improving safety and analysing actual statistics of accident rate in Europe and in the world. This topic describes how air accident can influence the popularity and economy conditions of airlines. At the end, based on the learnt knowledge, it suggests the optimal amount of finances that need to be invested in safety of commercial air transport.